Pengaruh Perbandingan Susu Kacang Tanah (Arachis hypogeae) Dan Susu Skim Terhadap Karakteristik Fisik Dan Kimia Susu Modifikasi - Arnett Paput, Fidel; Sugitha, I Made; Sri Wiadnyani, Anak Agung Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 4 (2022): Jurnal ITEPA, 2022)
This study aimed to determine the effect of comparison of peanut milk and skimmed milk towards physical and chemical characteristics of modified milk and to find out the right amount of peanut milk and skimmed milk to obtain the best characteristics of the modified milk. Peanuts that were used to make peanut milk were de-skinned, while skimmed milk used as cow milk. The experimental design used was Completely Randomized Design with the comparison of peanut milk and skimmed milk as a treatment which consist of 6 levels: 0%:100%, 10%:90%, 20%:80%. 30%:60%, and 50%:50%. The treatment was repeated three times, resulting in 18 experimental units. The data obtained than analyzed by Analysis of Variance, and if the treatments had a significant effect, continued with the Duncan Multiple Range Test. The result showed that the comparison of peanut milk and skimmed milk are significant effect on protein content, crude fiber, total ash content, fat, taste (scoring test), aroma (scoring test), and overall acceptance. The comparison of 30% peanut milk and 70% skimmed milk resulted in best characteristic with the criteria of: moisture content 87.88%, total ash content 0.59%, protein 3.81%, fat 3.43%, carbohydrate content 4.17%, crude fiber 3.34%, slightly peanut aroma, slightly peanut taste, and slighty liked overall acceptance